A physiotherapy-led transition to home intervention for older adults following Emergency Department discharge: a pilot feasibility randomised controlled trial - Mairéad Conneely; Aoife Leahy; Margaret O’Connor; Ahmed Gabr; Blessing Okpaje; Anastasia Saleh; Gillian Corey; Louise Barry; Anne Griffin; Íde O’Shaughnessy; Lorna Ryan; Ida O’Carroll; et al. (James Cook University, 2023)
Introduction: Older adults frequently attend the emergency department (ED) and experience high rates of adverse outcomes following ED presentation including functional decline, ED re-presentation and unplanned hospital admission. Our aim was to evaluate the feasibility of a physiotherapy-led integrated care intervention for older adults discharged from the ED (ED-PLUS).Methods: Older adults presenting to the ED with undifferentiated medical complaints and discharged within 72 hours were computer randomised in a ratio of 1:1:1 to deliver usual care, Comprehensive Geriatric Assessment (CGA) in the ED, or ED-PLUS (trial registration: NCT04983602). ED-PLUS is an evidence-based and stakeholder-informed intervention to bridge the care transition between the ED and community by initiating a CGA in the ED and implementing a 6-week, multi-component, self-management programme in the patient’s own home. Feasibility (recruitment and retention rates) and acceptability of the programme were assessed quantitatively and qualitatively. Functional decline was examined post-intervention using the Barthel Index. All outcomes were assessed by a research nurse blinded to group allocation.Results: Twenty-nine participants were recruited, indicating 97% of our recruitment target; 90% of participants completed the ED-PLUS intervention. All participants expressed positive feedback about the intervention. The incidence of functional decline at 6 weeks was 10% in the ED-PLUS group versus 70%-89% in the usual care and CGA-only groups.Discussion: High adherence and retention rates were observed among participants and preliminary findings indicate a lower incidence of functional decline in the ED-PLUS group. Recruitment challenges existed in the context of COVID-19. Data collection is ongoing for 6-month outcomes.